Research On the Use of Knowledge to Eliminate Waste in Enterprises in The Wielkopolskie Voivodeship - Natalia PAWLAK; Dominika DŁUGOŃSKA (Communications of International Proceedings, 2022)
This article presents the relationship between the level of knowledge of the concept of Lean Management and the tools used in this method and the degree of wastage in companies. The article examines whether companies in the Wielkopolska region use the knowledge of their employees to eliminate muda. The conducted research shows that managers in companies do not fully use the knowledge of lower-level employees working in the organization. It pays to listen to employees or create opportunities to use their ideas to eliminate waste.
Keywords: Lean Management-tool knowledge; muda; survey research; waste